Vicinal glutamates are better phosphomimetics: Phosphorylation is required for allosteric activation of guanylyl cyclase-A - Otto, Neil M.; Potter, Lincoln R. (Frontiers in Molecular Neuroscience, 2022)
Multisite phosphorylation of guanylyl cyclase (GC)-A, also known as NPR-A or NPR1, is required for receptor activation by natriuretic peptides (NPs) because alanine substitutions for the first four GC-A phosphorylation sites produce an enzyme that cannot be stimulated by NPs. In contrast, single Glu substitutions for the first six chemically identified GC-A phosphorylation sites to mimic the negative charge of phosphate produced an enzyme that is activated by NPs but had an elevated Michaelis constant (Km), resulting in low activity. Here, we show that vicinal (double adjacent) Glu substitutions for the same sites to mimic the two negative charges of phosphate produced a near wild type (WT) enzyme with a low Km. Unlike the enzyme with single glutamate substitutions, the vicinally substituted enzyme did not require the functionally identified Ser-473-Glu substitution to achieve WT-like activity. Importantly, the negative charge associated with either phosphorylation or glutamate substitutions was required for allosteric activation of GC-A by ATP. We conclude that vicinal Glu substitutions are better phosphomimetics than single Glu substitutions and that phosphorylation is required for allosteric activation of GC-A in the absence and presence of NP. Finally, we suggest that the putative functionally identified phosphorylation sites, Ser-473 in GC-A and Ser-489 in GC-B, are not phosphorylation sites at all.